Relação entre dinâmica clássica e transição de fase quântica em modelos de campos médio - Mauricio Reis e Silva Junior (2005)
In this work, we performed magnetophotoluminescence measurements up to 12 T in the temperature range of 2 K to 100 K in a sample composed by a single quantum well and in three double quantum wells made of InGaAs/InGaAlAs grown on a InP substrate by molecular beam epitaxy. Our aim was the quantification of the effective dimensionality , the binding energy b E and the effective mass of the excitons. The measurements were made in the four structures simultaneously, thus avoiding unwanted experimental variations when comparing the data. Through a selfconsistent fit of the luminescence peaks as a function of the magnetic field, we determined the values for , and b E for each structure. The binding energies were calculated theoretically through an analytic method which corrects the tridimensional exciton binding energy by a factor 2 / ( 1)2 , where 2 3 is determined by the effective confinement of the electrons and holes wavefunctions. Comparisonbetween the theoretical and experimental results for the different quantum wells has enabled us to check how the coupling of the wells affects the values of and b E for the InGaAs/InGaAlAs system.